1977
DOI: 10.1007/bf01406736
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid diverticula: A unitary approach to spinal cysts communicating with the subarachnoid space

Abstract: The authors report six cases of so-called spinal subdural arachnoid cysts, emphasizing the clinical and myelographic findings which, if not properly evaluated, may be misleading diagnostically. The literature of so-called perineural cysts and of extradural arachnoid cysts is likewise reviewed. Their clinical, roentgenological, and pathological features are examined. A common pathogenesis for all these lesions is proposed. It implies disruption and secondary proliferation of the arachnoid membrane. Hence, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(56 citation statements)
references
References 26 publications
2
50
0
3
Order By: Relevance
“…A literature review on the specified location of arachnoid cysts indicated that the mid-thoracic spine has the highest incidence among other vertebra for lesions, whereas the incidence for lesions on the cervical spine is relatively rare; however, a posterior cyst is more common than an anterior cyst. 6,10,11,13,14,17 Wang et al 6 postulated that the signs and symptoms of spinal arachnoid cysts are attributed to the chronic cyst expansion and the compression of the neural elements, while the preoperative symptoms and signs may be different according to the location of the cystic structure and compression of the spinal tracts. Anterior cysts tend to cause weakness and myelopathy, whereas dorsal cysts are present more commonly with neuropathic pain and numbness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on the specified location of arachnoid cysts indicated that the mid-thoracic spine has the highest incidence among other vertebra for lesions, whereas the incidence for lesions on the cervical spine is relatively rare; however, a posterior cyst is more common than an anterior cyst. 6,10,11,13,14,17 Wang et al 6 postulated that the signs and symptoms of spinal arachnoid cysts are attributed to the chronic cyst expansion and the compression of the neural elements, while the preoperative symptoms and signs may be different according to the location of the cystic structure and compression of the spinal tracts. Anterior cysts tend to cause weakness and myelopathy, whereas dorsal cysts are present more commonly with neuropathic pain and numbness.…”
Section: Discussionmentioning
confidence: 99%
“…Perret et al proposed that they are caused by diverticulum in the septum. 6,9 Fortuna et al 10,11 suggested that strangulation of the arachnoid granulations can produce cerebral spinal fluid (CSF), which becomes blocked by the arachnoid diverticulum. These fluid sequestrations lead to further disruption of the normal CSF flow, which can expand and cause syringomyelia.…”
Section: Introductionmentioning
confidence: 99%
“…4) Like syringomyelia, a number of different hypotheses have been proposed to explain the origin of spinal arachnoid cysts. 2,10) The true pathogenesis is likely to be multifactorial. Association of spinal arachnoid cysts and syringomyelia is rare and usually located in the thoracic region.…”
Section: Discussionmentioning
confidence: 99%
“…Teng and Rudner [8] proposed that normal variations of intraspinal CSF pressure lead to cyst formation through dilatation of low-resistance areas within the arachnoid; subsequent cyst enlargement is probably to be related to a one-way valve mechanism at the neck of the diverticulum. Fortuna et al suggested [9] that all types of congenital arachnoid diverticula result from hypertrophy, proliferation, and dilatation of arachnoid granulations; then if the dilatation is confined by a resistant dura, an intradural cyst would result, whereas a weakened or deficient dura would allow herniation of the arachnoid into the epidural space to form an extradural cyst.…”
Section: Patogenesismentioning
confidence: 99%